2021
DOI: 10.2991/absr.k.210621.070
|View full text |Cite
|
Sign up to set email alerts
|

The UV-VIS Spectrum Analysis From Silver Nanoparticles Synthesized Using Diospyros maritima Blume. Leaves Extract

Abstract: Research on the biological synthesis of silver nanoparticles (AgNPs) using plant extracts as reducing agents is growing rapidly because they are eco-friendly and cost-effective. Diospyros maritima Blume. is one of the plant species that had potential in the biosynthesis of AgNPs. In this study, biosynthesis of AgNPs was carried out by varying volume ratio of the extract and AgNO3 (5.0: 1; 2.0: 1; 0.5: 1; 0.2: 1; 0.1: 1) in reaction time (25 minutes, 2, 3, 24, 48, and 96 hours). The phytochemical screening resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
3
9
0
Order By: Relevance
“…While for CuO-NP solution, the absorption peak was observed between 200 and 250 nm. These values are consistent with those in the recent literature [24,25].…”
Section: Resultssupporting
confidence: 94%
“…While for CuO-NP solution, the absorption peak was observed between 200 and 250 nm. These values are consistent with those in the recent literature [24,25].…”
Section: Resultssupporting
confidence: 94%
“…In the current study, AgNPs produced a SPR peak of 445 nm compared to the crude extract, which did not reveal any absorption peaks. The appearance of an absorption peak at a wavelength of 400-500 nm is an indication that AgNPs were formed [30]. Similar studies reported the UV-visible spectrum of AgNPs biosynthesized from the extracts of A. sieberi at 482 nm [31], 407 nm [32], and 410 nm [33].…”
Section: Discussionsupporting
confidence: 67%
“…The longitudinal band occurs at higher wavelengths relative to the transverse band in elongated structures. In our case 426 nm corresponds to transverse mode and 696 nm corresponds to longitudinal mode of AgNDs ( Agustina et al., 2020 ; Bijanzadeh et al., 2012 ; Cheng et al., 2019a , 2019b , 2019c ; Wang et al., 2021 ). The dip is predominant for longitudinal mode relative to the transverse mode indicating a greater anisotropy.…”
Section: Resultsmentioning
confidence: 91%